COVID : the politics of fear and the power of science - Siegel, Marc (Marc K.) (Nashville, Tennessee : Turner Publishing Company, 2020)
Life for citizens of the developed world before the pandemic was safer, easier, and healthier than for any other people in history thanks to modern medicine, science, technology, and intelligence---but COVID-19 has stolen that security and our nation's peace of mind. Now there is a pandemic virus, as well as a crippling epidemic of fear sweeping America. Why? The answer, according to nationally renowned health commentator Dr. Marc Siegel, is that we already lived in an artificially created culture of fear that was just waiting to be unleashed. In COVID: The Politics of Fear and the Power of Science, Siegel identifies three major catalysts of the culture of fear: government, the media, and our own psyche. With fascinating, blow-by-blow analyses of the most sensational false alarms of the past few years, compounded now by the worst contagion of our lifetimes, he shows how fear mongers manipulate our most primitive instincts--often without our even realizing it. COVID shows us how to look behind the hype and hysteria, inoculate ourselves against these crippling fear tactics, and develop the emotional and intellectual skills needed to take back our lives, even as we battle the pandemic itself.
Part one, pre-COVID -- Fight or flight -- It works for animals but not for us -- Our culture of worry -- Playing politics with fear: post 9/11 -- False evidence, assumed risk -- SARS: the first coronavirus outbreak -- The fear prophets -- Is there a cure for fear? -- Bird flu and swine flu -- Swine flu, the last pandemic -- Ebola: outbreaks in Africa cause panic here -- Zika: facts and fears -- Part two, COVID -- What we don't know does hurt us: China and the WHO -- Science versus the politics of COVID -- Lockdowns and the politics of fear -- The president: in real time -- Fear props: masks -- Operation warp speed -- The politics of fear: mental health and schools -- More fear props -- Fear leaders in the time of COVID.
Includes bibliographical references.
Keywords: COVID-19 (Disease); COVID-19 (Disease) -- Political aspects; Epidemics -- Political aspects; Fear -- Political aspects